Upaya Hukum Bagi Ahli Waris Pengganti Dalam Mempertahankan Hak Warisannya - Maftukhin Maftukhin (DE RECHT (Journal of Police and Law Enforcement), 2025)
In the study of inheritance law, we will study the question of who and what is being studied in this field, namely heirs, heirs and inheritance. In this article the author will examine the legal rules related to the position of substitute heirs who replace their parents to obtain inheritance. of an heir who has died, do not let his position and rights be eliminated, just because that party has the status of a substitute heir who replaced the position of his parents who died before the heir, therefore the writing of this article is focused on exploring what legal remedies should be taken. carried out by the successor heirs in order he gets his rights and how much part the replacement heir should get if he gets inheritance property. This research uses the library research method (Library Library), with a normative legal study approach, then the legal rule is obtained, namely that the replacement heir can file a lawsuit for the distribution of inheritance assets in the religious court where the testator dies, and receives the same share as the living heirs.